(untitled) (International journal of artificial intelligence, 2025)
This article explores how educational service providers, such as universities and online platforms, can strengthen their export-oriented competitive strategies to attract international students and succeed in the global education market. It outlines the concept, identifies key challenges, and proposes actionable strategies supported by statistics and real-world examples. The discussion emphasizes academic innovation, partnerships, technology, and student support to address regulatory, cultural, and competitive barriers.